2011
DOI: 10.1210/en.2011-1205
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone-Producing Adenoma Formation in the Adrenal Cortex Involves Expression of Stem/Progenitor Cell Markers

Abstract: Aldosterone producing adenoma (APA) is the most common form of surgically curable hypertension. To further understand mechanisms involved in APA formation, we investigated the expression of molecules linked to adrenal stem/precursor cells [β-catenin, Sonic hedgehog (Shh), CD56], and nuclear receptors that play key roles in adrenocortical development and function steroidogenic factor 1, dosage-sensitive sex reversal-adrenal hypoplasia congenita critical region on the X chromosome, gene 1) in six control adrenal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 43 publications
3
80
2
Order By: Relevance
“…This is supported by 2 subsequent transcriptome analyses performed in our laboratory on 123 APA samples and 11 control adrenals, which showed a subgroup structure that could reflect distinct pathogenic mechanisms and which was confirmed by functional pathological investigations. 40,41 Nevertheless, CYP11B2 expression appears to be consistently increased, although to variable extent, among APA samples, with low expression of CYP11B2 in APA being a rare finding. 42 …”
Section: From Physiological To Pathological Aldosterone Productionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is supported by 2 subsequent transcriptome analyses performed in our laboratory on 123 APA samples and 11 control adrenals, which showed a subgroup structure that could reflect distinct pathogenic mechanisms and which was confirmed by functional pathological investigations. 40,41 Nevertheless, CYP11B2 expression appears to be consistently increased, although to variable extent, among APA samples, with low expression of CYP11B2 in APA being a rare finding. 42 …”
Section: From Physiological To Pathological Aldosterone Productionmentioning
confidence: 98%
“…Recently, we have shown that activation of ␤-catenin occurs in approximately two thirds of APAs. 41 However, ␤-catenin activation status was not associated with any biological or clinical parameters. Moreover, the sequencing of exons 3 and 5 of the CTNNB1 gene in tumor DNA from 41 patients did not show mutations that could account for ␤-catenin activation.…”
mentioning
confidence: 92%
“…Nevertheless, despite their morphological appearance, ZF-like cells still express markers of the ZG cells such as CYP11B2, DAB2, or CD56, suggesting that adenoma cells derive from ZG (Boulkroun et al 2010(Boulkroun et al , 2011. In different studies, mutational status of the tumor has been shown to be correlated with its cellular composition and size: KCNJ5 mutations were associated with large ZF-like APA, while ATP1A1 and CACNA1D mutations were associated with small ZG-like APA, suggesting that adenoma size is associated with cellular composition (Azizan et al 2012, Dekkers et al 2014.…”
Section: Familial Hyperaldosteronism Type IImentioning
confidence: 99%
“…Our actual knowledge does not allow explanation of the mechanisms involved in APA formation and their histological variability. Different hypotheses have been formulated: i) if APA derive from ZG cells, the ZF-like phenotype would be due to greater metabolic activity or induction of lipid uptake (Boulkroun et al 2010(Boulkroun et al , 2011; ii) if APA derive from ZF cells, AS expression would be due to the presence of a somatic mutation in identified or not yet identified genes (Azizan et al 2012(Azizan et al , 2013; iii) APA derive from aldosteroneproducing cell clusters (APCCs; Nishimoto et al 2010). APCCs are AS-positive cell clusters of cuneiform or trapezoid shape located in the ZG and outer ZF that were reported recently in addition to the conventional adrenal cortex zonation (Nishimoto et al 2010).…”
Section: Familial Hyperaldosteronism Type IImentioning
confidence: 99%
See 1 more Smart Citation